Digital Platforms Use among Postgraduate Faculty to Enhance University Visibility - Ramírez-García, Adán Guillermo (2025)
The internet has democratized the visibility of university-led research, while social media has increased connectivity within the digital ecosystem, helping to reduce the digital divide in academia and expand its contributions to society. This study examines both the presence and prevalence of digital platform use among a group of professors of the Rural Regional Development Masters Course at the Chapingo Autonomous University in Mexico. The study also aims to identify notable disparities among those professors in study group who are members of the National System of Researchers (SNII) and those who are not. The objective is to assess how management of faculty digital profiles influences university visibility. The study consisted of a quantitative methodology based on an exploratory paradigm and cross-sectional design. Data was collected from a sample group at a single point in time and systematized using observational techniques and a review of digital platforms. The findings reveal that the professors participating in the study group had minimal presence on academic social media and limited involvement in managing their digital identities, regardless of SNII affiliation. It can be concluded that a university´s online presence and reputation, as determined by webometric rankings, can be strengthened when faculty effectively manage their digital identities, as determined by webometric rankings. Universities could, therefore, benefit from developing and implementing targeted strategies to train faculty in effectively using social media and in enhancing their online presence.